Hepatopulmonary Fistula in a Colorectal Cancer Patient - Maria João Silva; Nuno Almeida Costa; Susana Dias; Maria José Sousa; Maria Fragoso (Case Reports in Hepatology)
Cancer patients with liver metastasis may be candidates for liver surgery and local interventional techniques as part of their treatment. Although rare in this setting, hepatopulmonary fistula has been described as a possible complication. The clinical picture may be atypical, and, without specific treatment, it usually has a dismal prognosis. As locoregional treatments (whether interventional or surgical techniques) in liver neoplasms are being more frequently used we need to include this entity as a possible differential diagnosis of local liver treatment complications.